2021
DOI: 10.1519/jsc.0000000000003989
|View full text |Cite
|
Sign up to set email alerts
|

Training, Supplementation, and Pharmacological Practices of Competitive Male Bodybuilders Across Training Phases

Abstract: Hackett, DA. Training, supplementation, and pharmacological practices of competitive male bodybuilders across training phases. J Strength Cond Res 36(4): 963–970, 2022—Bodybuilding involves the pursuit of muscularity and leanness primarily through the use of progressive resistance training in combination with other practices such as manipulation of diet and use of ergogenic aids. This study aimed to compare the training practices and ergogenic aids used by competitive male bodybuilders across training phases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
60
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 47 publications
8
60
0
Order By: Relevance
“…The majority of the studies included adult athletes, some included under 18 athletes [ 20 , 24 , 25 , 28 , 32 , 34 , 38 , 39 , 40 ], and none included older-adult athletes. Most studies included athletes from several sport categories [ 6 , 15 , 20 , 21 , 22 , 27 , 31 , 34 , 36 , 37 , 38 , 40 ], while others focused on one type of sport such as running [ 23 , 24 ], bodybuilding [ 41 , 42 ], football [ 32 , 35 ], rowing [ 26 ], sailing [ 25 ], rugby [ 30 ], fencing [ 28 ], handball [ 29 ], squash [ 33 ], and track and field [ 39 ]. Interestingly, one study focused on paralympic sports [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies included adult athletes, some included under 18 athletes [ 20 , 24 , 25 , 28 , 32 , 34 , 38 , 39 , 40 ], and none included older-adult athletes. Most studies included athletes from several sport categories [ 6 , 15 , 20 , 21 , 22 , 27 , 31 , 34 , 36 , 37 , 38 , 40 ], while others focused on one type of sport such as running [ 23 , 24 ], bodybuilding [ 41 , 42 ], football [ 32 , 35 ], rowing [ 26 ], sailing [ 25 ], rugby [ 30 ], fencing [ 28 ], handball [ 29 ], squash [ 33 ], and track and field [ 39 ]. Interestingly, one study focused on paralympic sports [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies used self-reported questionnaires or surveys to collect data on dietary supplement use among athletes. Some studies have provided their questionnaire or survey in an online format [ 24 , 27 , 29 , 32 , 37 , 40 , 41 ]. However, the selected reporting timeframe varied across studies ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…These objectives require the implementation of a diverse array of strategies to optimize physique aesthetics on show-day. Preparation for bodybuilding competition generally involves two phases: an off-season phase, in which the primary goal is to optimize muscle hypertrophy; and a pre-contest phase, in which the focus is to reduce subcutaneous body fat as low as possible while simultaneously maintaining muscle mass [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Competitive bodybuilding pushes the limits of resistance training adaptations and requires dedication to rigorous training and strict dietary regimes [ 1 , 5 ]. Over 95% of bodybuilders use dietary supplements [ 6 ], with the two most common being creatine monohydrate and protein [ 5 , 6 ]. Non-nutritional, performance-enhancing drugs, such as veterinary-grade vitamin supplementation, often in alarming quantities, and/or anabolic–androgenic steroids (AAS) are also used [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over 95% of bodybuilders use dietary supplements [ 6 ], with the two most common being creatine monohydrate and protein [ 5 , 6 ]. Non-nutritional, performance-enhancing drugs, such as veterinary-grade vitamin supplementation, often in alarming quantities, and/or anabolic–androgenic steroids (AAS) are also used [ 6 , 7 , 8 ]. Most of the extreme nutritional, drug and training strategies used in bodybuilding are derived from non-evidence-based sources [ 1 , 2 , 5 ], giving rise to increasing concerns about their potential adverse health impact [ 9 ].…”
Section: Introductionmentioning
confidence: 99%